Poenostavljena prisilna poravnava - Leskovec, Borut (Podjetje in delo, 2018)
The author discusses the legal effects of the simplified compulsory settlement, focusing on the question if and in which cases the final court decision on confirmation of simplified compulsory settlement is considered an enforceable instrument. There are two ways to vote on the simplified compulsory settlement - by ballot papers or by an agreement on adoption of the simplified compulsory settlement, concluded between the insolvent debtor and its creditors in the form of a directly enforceable notarial deed. Only the combination of the latter and the final decision on confirmation of the simplified compulsory settlement represents an enforceable instrument. In practice, there are problems due to lack of uniformity of case law, which is adopting contradictory decisions.
Keywords: enforceability; enforceable instrument; izvršilni naslov; izvršljivost; poenostavljena prisilna poravnava; simplified compulsory settlement